PENINGKATAN PEMBERDAYAAN PELAYANAN PUBLIK - H. Abdul Rasul (AkMen JURNAL ILMIAH, 2018)
The purpose of this research is to know how to improve public service empowerment for society. The results of this study are For the service user community, empowerment approach can facilitate them to access information service, controlling the implementation of services, and obtain their dignity and position as a sovereign citizen.But most importantly, through empowerment of public services all parties good government bureaucracy , staktholders, and the service user community, can realize that the responsibility of the quality of public services is essentially a shared responsibility.